Compte supprimé
30

# Développer et réduire les expressions suivantes : A(x) = (2x+1)(x-3)-4x+1 B(x) = (4x-5)² C(x) = 2(x-1)(x+3) D(x) = (-2x+1)(x+3)-2(x-5) E(x) = 3(4x+3)(x+1)+(x+1)² F = (3x-1)(2x+5)-3(x+1)(x-2) G(x) = (3x-2)² - 3(x+2)(4x-3)

(1) Réponses
Alicia1016

A(x) = (2x+1)(x-3) - 4x+1 A(x) = 2x² - 6x +x - 3 - 4x + 1 A(x) = 2x² - 9x - 2 B(x) = (4x-5)² B(x) = (4x)² - 2 x 4x x5 + 5² B(x) = 16x² - 40x + 25 C(x) = 2(x-1)(x+3) C(x) = 2 (x² + 3x - x - 3) C(x) = 2( x² + 2x - 3) C(x) = 2x² + 4x - 6 D(x) = (-2x+1)(x+3)-2(x-5) D(x) = - 2x² - 6x + x + 3 - 2x + 10 D(x) = - 2x² - 7x + 13 E(x) = 3(4x+3)(x+1)+(x+1)²  E(x) = 3( 4x² + 4x + 3x + 3) + ( x² + 2x + 1) E(x) = 3( 4x² + 7x + 3) + x² + 2x + 1 E(x) = 12x² + 21x + 9 + x² + 2x + 1 E(x) = 13x² + 23x + 10 F = (3x-1)(2x+5)-3(x+1)(x-2) f(x) =( 6x² + 15x - 2x - 5) - 3(x² - 2x + x - 2) f(x) = (6x² + 13x - 5 )- 3 (x² - x - 2) f(x) = 6x² + 13x - 5 - 3x² + 3x + 6 f(x) = 3x² + 16x + 1 G(x) = (3x-2)² - 3(x+2)(4x-3) G(x) = (9x² - 12x + 4) - 3 ( 4x² - 3x + 8x - 6) G(x) = 9x² - 12x + 4 - 3 ( 4x² + 5x - 6) G(x) = 9x² - 12x + 4 - 12x² - 15x + 18 G(x) = - 3x² - 27x + 22

Ajouter une réponse